PREFERENCIAS DE CONSUMO DE ACEITE DE OLIVA EN ENSENADA, BAJA CALIFORNIA - Laura Cuevas Monzón; Lino Meraz Ruiz (European Scientific Journal, ESJ, 2015)
Currently, there is a great acceptance among consumers for olive oil because this product has properties beneficial to health. However, the production in México is almost zero; most are imported mainly from Spain. Nevertheless, in Ensenada, Baja California (México), they are made one of the best olive oils of the region and the world. Therefore, this research is characterized as descriptive non-experimental design, which aims to describe the preferences in the consumption of olive oil by local market (Ensenada). For this purpose, a structured survey comprised seven questions was applied to a non-random sample of 20 people randomly designed. The results found that a large proportion of subjects buy this product (85%) directly from the supermarket (100%), with a frequency of every three months (45%) and almost all of the oils offered on the market are from Spain, lacking a local or regional brand. In conclusion, further study on this subject in which more accurate measurement parameters are established and to measure the correlation between the level of education, age and sex with the consumption of olive oil is suggested.